Evaluation of the Effect of Astragalus membranaceus Saponins Administration on Knee Function and Cartilage Biomarkers in Healthy Subjects with Knee Discomfort. - Zhuang, Shu Ru; Leong, Pui-Ying; Chiang, Hsin-Pei; Shen, You-Cheng (Nutrients, 2026)
Objective: This study aimed to evaluate the effects of 12 weeks of Astragalus membranaceus saponins (AMS) supplementation on functional performance, knee joint mobility, self-reported outcomes, and biomarkers of inflammation and cartilage in healthy subjects with knee discomfort. Methods: A randomized, double-blind, placebo-controlled trial was conducted in healthy subjects aged 20–70 years with knee discomfort but without clinically diagnosed knee osteoarthritis. Participants were assigned to receive one capsule of AMS or a placebo once daily for 12 weeks. The pre-specified primary endpoints were the SLSD step count and knee ROM; KOOS total score was a key secondary endpoint; serum biomarkers were exploratory. The results included functional performance assessed by the Single Leg Step Down (SLSD) test, knee range of motion (ROM), and self-reported outcomes using the Knee injury and Osteoarthritis Outcome Score (KOOS). Knee ROM was measured with a goniometer and recorded as both active ROM and passive ROM for knee flexion and extension. Serum biomarkers of inflammation (IL-8, IL-1β, MIP-1α), cartilage degradation (CTX-II, COMP, MMP-13, COL2A1), and cartilage synthesis (PIINP) were evaluated at baseline and Week 12. Results: Within the AMS group, SLSD step count increased significantly by 16.83% (Δ = +12.78 steps; p < 0.05) and recovery time decreased significantly by 19.12% (Δ = −108.91 s; p < 0.05) compared with baseline, whereas the placebo group showed smaller, non-significant changes (+4.48 steps and −56.48 s, respectively); however, neither between-group difference in change scores reached statistical significance. Significant improvements in active and passive knee ROM were observed in both flexion and extension (all p < 0.05) within the AMS group, whereas the placebo group showed no significant changes. KOOSs improved significantly in all domains within the AMS group, with the largest gains observed in sport/recreation (+22.23%) and quality of life (+18.38%). In the exploratory biomarker analysis, several inflammation and cartilage-related biomarkers changed after AMS supplementation showed within-group reductions (IL-8, COMP, MMP-13) and PIINP increased. Conclusions: 12 weeks of AMS supplementation was associated with improvements in selected functional, mobility, and outcomes in generally healthy adults with self-reported knee discomfort. AMS was also associated with changes in selected circulating biomarkers related to inflammation and cartilage metabolism. These findings should be interpreted as a preliminary, safe, complementary strategy to support joint health in healthy subjects with knee discomfort.